Achievement Goals and Levels of Satisfaction towards the Degree in Pre-School and Primary Education Teaching - Viciana-Garófano, Virginia (2017)
This research aims to know the level of satisfaction and achievement goals of students enrolled in seventh semester of the Degree in Pre-School and Primary Education Teaching. This empirical study analyses the relation between gender, specialization, student satisfaction, and achievement goals in a sample of 293 respondents in their last year of university; they study in two universities located in Granada (Spain), which are the Faculty of Educational Sciences-FCCE (public institution), and the University School-La Inmaculada (private university). A quantitative, descriptive, and cross-sectional design was used to develop a relational study to analyze the degree of dependence between achievement goals, student satisfaction, gender, and attainment of degrees. The results showed that the students enrolled in the Degree in Pre-School and Primary Education Teaching are satisfied with their degree; they highlighted the performance of teamwork and the quality of the teachers. In addition, students emphasized the attention teachers paid to them, their punctuality, and the low absenteeism. Furthermore, men are frequently associated with competitiveness, high performance achievement, and results. In the opposite, women are related with task-orientation, carrying it out with a greater competence.